The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ajog.2018.01.043
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of knotless barbed suture vs conventional suture for closure of the uterine incision at cesarean delivery

Abstract: The use of a knotless barbed suture is a reasonable alternative to conventional sutures because it reduced the closure time of the uterine incision. There was also less need for additional hemostatic sutures and slightly reduced estimated blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“… 4 , 13 15 , 36 , 50 61 Two RCTs were also performed comparing barbed suture compared with standard suture for uterine closure. 62 , 63 In addition to single- compared with two-layer closure, a distinction is made in some RCTs regarding locked or unlocked suture technique. Primary outcomes vary between operating time, blood loss, and postpartum ultrasound measurement of the residual myometrial thickness.…”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“… 4 , 13 15 , 36 , 50 61 Two RCTs were also performed comparing barbed suture compared with standard suture for uterine closure. 62 , 63 In addition to single- compared with two-layer closure, a distinction is made in some RCTs regarding locked or unlocked suture technique. Primary outcomes vary between operating time, blood loss, and postpartum ultrasound measurement of the residual myometrial thickness.…”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%
“…My colleagues and I thank Dr Abraham for her interest in our randomized study on the use of knotless barbed suture for closure of the uterine incision at cesarean delivery. 1 We agree that the time saved and decrease in blood loss, although statistically significant, may not be clinically significant. Any advantage must be weighed against the cost of the suture, but as you are aware this cost difference is very small compared to the total hospital bill that could be anticipated from a cesarean delivery.…”
Section: Replymentioning
confidence: 60%
“…A randomized clinical trial of knotless barbed suture vs conventional suture for closure of the uterine incision at cesarean delivery TO THE EDITORS: I am commenting on the article by Peleg et al 1 in which use of knotless barbed suture and polyglactin suture for uterine incision closure at time of cesarean were compared. The authors concluded that use of a knotless barbed suture was associated with a reduction in uterine incision closure time, need for additional hemostatic sutures, and estimated blood loss compared to use of polyglactin.…”
mentioning
confidence: 99%
“…We were excited to read the study, A randomized clinical trial of knotless barbed suture vs conventional suture for closure of the uterine incision at cesarean delivery, by Peleg et al 1 The authors did a fine job of designing a study in this burgeoning niche and summarizing their findings clearly.…”
Section: To the Editorsmentioning
confidence: 99%
“…Early diagnosis in endometrial cancer minimizes the impact of treatments TO THE EDITORS: We read with interest the paper from the Israeli Gynecology Oncology Group published by Gemer et al 1 The authors investigated whether asymptomatic postmenopausal patients have a survival benefit in comparison with symptomatic patients. Analyzing a large amount of data of women with endometrial cancer, the authors observed that women receiving an incidental diagnosis of endometrial cancer have no better outcomes than patients with compelling symptoms (ie, vaginal bleeding).…”
Section: To the Editorsmentioning
confidence: 99%